Attitude change towards the practice of medicine during medical education among University of the Philippines College of Medicine students - Manapat-Reyes, Bernadette Heizel D.
The development of attitudes during medical education is a function of maturity and learning gleaned from the formal as well as the operational and informal curricula. The curricular experience is hoped to affect the development of attitudes that the institution holds. Thus, this project was conducted to determine if a relationship exists between medical education and students' attitudes towards the practice of medicine at the UP College of Medicine. It set out to describe the degree of expression of certain attitude highlighted in the mission-vision statement of the College, compare the attitudes of students among the different year levels, and between the direct and lateral entrants to the INTARMED program. This was done by conducting a cross-sectional survey among a random sample of 308 students from year levels 3 to 7, using an especially designed questionnaire designed to track consistency in their statements of beliefs, feelings and actions regarding particular attitude objects. Responses were presented as mean scores on a scale of 1.00 to 4.00, with the latter being the highest possible score obtained per construct. The results and findings support the hypothesis that a relationship exists between medical education and the students' attitudes towards the practice of medicine. Some attitudes were very favorably expressed, obtaining mean scores of =3.00 for each construct on the scale given. These scores for the largely cognitive constructs of dedication to learning (3.42) and responsibility (3.31), some of the professional attributes of a physician such as humanism (3.27) and compassion (3.10), and attitudes that correspond to the development of social responsibility as social awareness (3.11) and nationalism (3.04). Other attitude constructs were favorably expressed, with mean scores between 2.75 and 3.00. These included respect for rights of others (2.73), respect for privacy (2.82) and community-orientation (2.90). For these attitudes there was inconsistency of expression of beliefs, feelings and actions pertaining to the particular constructs. There was no difference in the attitudes of lateral and direct entrants to the INTARMED program. However, the degree of expression of most of these attitudes varied amongst the different year levels, except for dedication to learning, which was consistently expressed from year levels 3 to 7. Students who have just completed internship had generally lower mean scores for most constructs. These findings are contrary to the hoped for enhancement of the degree and consistency in which attitudes advocated by the College should be developed. In general, although the study did display a favorable expression of most attitudes towards the practice of medicine, the relationship between medical education and the development of attitudes appeared to be converse for most attitude objects. The medical experience did not appear to be successful in promoting the growth of attitudes that the College advocates.